Mentoring Perceptions and Experiences among Nigerian Undergraduate Dental Students - Bolu Adeoti; Olayinka Donald Otuyemi (Nigerian Dental Association, 2024)
Introduction: Mentoring among undergraduate dental students in Nigeria has never been evaluated, despite being well reported, to improve academic performance and learning process globally. This study assessed perceptions and experiences of Nigerian undergraduate dental students to mentoring. Materials and Methods: A sample of 382 students was recruited across all the thirteen Nigerian dental faculties. A self-administered online questionnaire prepared on google form was sent to the students for completion. The completed forms were analyzed using SPSS version 20. Descriptive and analytical statistics were applied, and set the statistical significant level at P<0.05. Results: The students showed a very good knowledge of mentoring (99.0%) and an adequate understanding of the role of a mentor (67.3%). Many students had experienced mentoring prior to their dental training; mainly from religious institutions (60.0%). The majority (96.1%) of the students would have preferred to be mentored at the start of their training; however, only 21.2% had assigned mentors. More than half (57.6%) of the students would have preferred to choose their mentor, and the majority (43.2%) were indifferent about gender preference of a mentor. About two-thirds of the students perceived career development as the most important reason for mentoring. The benefits of mentoring were ranked very highly, especially among the female students. Gender was the only predictor for successful mentoring (P< 0.05). Conclusions: Dental students reported low faculty mentoring. Career development was perceived as the most important factor in mentoring. Students recommended that mentoring should be incorporated into the dental curriculum right from the commencement of their training.    Keywords: mentoring, perceptions, experiences, dental students, Nigerian undergraduates